(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Although economically advantageous, tourism growth can present considerable challenges to local communities and natural environments if not properly managed. This study examines domestic tourists’ perceptions of Social Carrying Capacity (SCC) on Pangkor Island, Perak, a well-known tourism destination in Malaysia. A quantitative approach was used to collect data from 92 domestic tourists through structured questionnaires and the People at One Time (PAOT) visual assessment method to assess perceived crowding during peak periods. Most respondents (84.8%) indicated that their visit was for holidays and leisure. Results demonstrate a moderate level of satisfaction with infrastructure, especially in transport services (mean = 3.27). However, concerns were identified regarding cleanliness (mean = 3.01), crowding (mean = 2.25), and interaction with local communities (mean = 2.29). Findings from the PAOT showed that moderate crowding levels were deemed acceptable, with 39.1% of the respondents selecting Image C and 37.0% selecting Image D. The study emphasises the necessity of ongoing monitoring and increased community engagement, despite current SCC indicators being within acceptable thresholds, to ensure a balance between tourism development and the quality of life for residents. The findings provide valuable insights for policymakers and tourism planners focused on sustainable destination management in coastal and island contexts.